Matricaria chamomilla: an Updated Review on Biological Activities of the Plant and Constituents - Mina Saeedi; Mahnaz Khanavi; Kasra Shahsavari; Azadeh Manayi* (Iranian Society of Pharmacognosy, 2024)
Chamomile or camomile (Matricaria chamomilla L. syn. Matricaria recutita L.) belongs to the family Asteraceae. It is native to Europe and West Asia and has spread to other parts of the world. The plant essential oils and extracts have been frequently used for thousands of years in traditional and folk medicines across the world, due to their valuable medicinal properties. Currently, it is widely applied in different industries such as pharmaceutical, cosmetics, and food industry. Herein, the literature was carefully reviewed via search engines such as Google Scholar, Pub Med, and Scopus using keywords including biological activity, chamomile, flavonoids, pharmacological activity, Matricaria chamomilla, and Matricaria recutita. Sesquiterpenes such as bisabolol oxide B, bisabolone oxide, and bisabolol oxide A have been identified as the major constituents of chamomile essential oil. Also, various phenolic compounds and flavonoids were mostly reported as active compounds in the plant extracts. Although there are various reports pinpointing the mechanisms of action of chamomile and its constituents, some points have remained ambiguous and further well-designed clinical trials are required. Focusing on the importance of valuable biological properties of chamomile, the present review precisely discussed the characterized chemical constituents of the plant along with their mechanisms of action.